Heart failure patients without echocardiography are more commonly diagnosed in hospital care and are associated with higher mortality compared to primary care - Viktor Samskog; Jason Davidge; Anders Halling; Björn Agvall (Taylor & Francis Group, 2024)
AbstractObjective This Swedish study aimed to assess the prevalence, associated clinical factors, and mortality rates of heart failure patients diagnosed without echocardiograms in both hospital and primary care settings.Design We conducted a retrospective population-based study using data from the Region Halland healthcare database in Sweden covering 330,000 residents.Subjects From 2013-2019, 3,903 patients received an incidental heart failure diagnosis without an echocardiogram and they were followed for one year.Main outcome measures Using logistic and Cox regression analyses, we evaluated the prevalence, clinical characteristics, and all-cause mortality at intervals of 30, 100, and 365 days post-diagnosis.Results In this Swedish cohort, the one-year all-cause mortality rate was markedly higher for patients diagnosed in hospitals (42%) compared to those in primary care (20%, p < 0.001). Patients diagnosed in primary care were older and had fewer comorbidities and lower NT-proBNP levels. Hospital-diagnosed patients faced a significantly higher mortality rate in the initial 30 days but saw similar rates to primary care patients thereafter.Conclusion In a Swedish region, heart failure diagnoses without echocardiograms were more common in hospitals, and these patients initially faced worse prognoses. After the first month, however, the prognosis of hospital-diagnosed patients mirrored that of those diagnosed in primary care. These findings emphasize the need for improved diagnostic and treatment approaches in both care settings to enhance outcomes.